TNFα-mediated activation of NF-κB downregulates sodium-iodide symporter expression in thyroid cells - Faria, Márcia (2021)
The sodium-iodide symporter (NIS) mediates transport of iodide across the basolateral membrane of thyroid cells. NIS expression in thyroid cancer (TC) cells allows the use of radioactive iodine (RAI) as a diagnostic and therapeutic tool, being RAI therapy the systemic treatment of choice for metastatic disease. Still, a significant proportion of patients with advanced TC lose the ability to respond to RAI therapy and no effective alternative therapies are available. Defective NIS expression is the main reason for impaired iodide uptake in TC and NIS downregulation has been associated with several pathways linked to malignant transformation. NF-κB signaling is one of the pathways associated with TC. Interestingly, NIS expression can be negatively regulated by TNF-α, a bona fide activator of NF-κB with a central role in thyroid autoimmunity. This prompted us to clarify NF-kB's role in this process. We confirmed that TNF-α leads to downregulation of TSH-induced NIS expression in non-neoplastic thyroid follicular cell-derived models. Notably, a similar effect was observed when NF-κB activation was triggered independently of ligand-receptor specificity, using phorbol-myristate-acetate (PMA). TNF-α and PMA downregulation of NIS expression was reverted when NF-κB-dependent transcription was blocked, demonstrating the requirement for NF-kB activity. Additionally, TNF-α and PMA were shown to have a negative impact on TSH-induced iodide uptake, consistent with the observed transcriptional downregulation of NIS. Our data support the involvement of NF-κB-directed transcription in the modulation of NIS expression, where up- or down-regulation of NIS depends on the combined output to NF-κB of several converging pathways. A better understanding of the mechanisms underlying NIS expression in the context of normal thyroid physiology may guide the development of pharmacological strategies to increase the efficiency of iodide uptake. Such strategies would be extremely useful in improving the response to RAI therapy in refractory-TC.